2020
DOI: 10.3389/fcell.2020.572276
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Hypoxia Decreases Expression of NOTCH3, HEY1, CC10, and FOXJ1 via NKX2-1 Downregulation and Intermittent Hypoxia-Reoxygenation Increases Expression of BMP4, NOTCH1, MKI67, OCT4, and MUC5AC via HIF1A Upregulation in Human Bronchial Epithelial Cells

Abstract: Previous studies have shown that the experimental models of hypoxia-reoxygenation (H/R) mimics the physiological conditions of ischemia-reperfusion and induce oxidative stress and injury in various types of organs, tissues, and cells, both in vivo and in vitro, including human lung adenocarcinoma epithelial cells. Nonetheless, it had not been reported whether H/R affected proliferation, apoptosis, and expression of stem/progenitor cell markers in the bronchial epithelial cells. In this study, we investigated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Moreover, preclinical and clinical lung transplantation studies also demonstrated that Tregs and their associated mediators modulate both airway epithelium and vascular endothelium of grafted tissue, which effectively modulates the expression of various adhesion proteins on the surface of both airway epithelium and microvessels within the graft [22][23][24][25][26][27][28][29][30][31]. Inflammation-associated airway epithelial, ciliary loss, and vascular endothelial injury have been reported in various preclinical and clinical transplantation studies [22,23,[32][33][34]. FOXJ1 has been associated with ciliogenesis in airway epithelium and affected largely due to the severe hypoxic and ischemic state of the tissue [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, preclinical and clinical lung transplantation studies also demonstrated that Tregs and their associated mediators modulate both airway epithelium and vascular endothelium of grafted tissue, which effectively modulates the expression of various adhesion proteins on the surface of both airway epithelium and microvessels within the graft [22][23][24][25][26][27][28][29][30][31]. Inflammation-associated airway epithelial, ciliary loss, and vascular endothelial injury have been reported in various preclinical and clinical transplantation studies [22,23,[32][33][34]. FOXJ1 has been associated with ciliogenesis in airway epithelium and affected largely due to the severe hypoxic and ischemic state of the tissue [34].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation-associated airway epithelial, ciliary loss, and vascular endothelial injury have been reported in various preclinical and clinical transplantation studies [22,23,[32][33][34]. FOXJ1 has been associated with ciliogenesis in airway epithelium and affected largely due to the severe hypoxic and ischemic state of the tissue [34]. β-Catenin plays a vital role in cell survival and proliferation; however, little is known regarding its role in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly cell-line models have also demonstrated increased oxidative stress, increased pro-inflammatory mediators, reduced anti-inflammatory mediators and reduced surfactant proteins 10 . Many effects of hypoxia can be induced both via continuous hypoxia or by hypoxia/reoxygenation events 12,11,10 , both of which can be found in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this there is a scarcity of data regarding the direct impacts of hypoxia on lung cellular behaviour. The limited evidence available has shown a number of effects including increased oxidative stress, inflammatory markers, and pro-apoptotic genes in animal models [10][11][12] . Similarly cellline models have also demonstrated increased oxidative stress, increased pro-inflammatory mediators, reduced anti-inflammatory mediators and reduced surfactant proteins 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation